A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin. Issue 2 (17th January 2020) - Zhou, Yi; Jin, Mei; Jin, Chunshi; Ye, Chao; Wang, Jiaming; Sun, Jinfeng; Wei, Cheng-Xi; Zhou, Wei; Li, Gao
Abstract: One new aryldihydronaphthalene-type lignan (1 ) together with eight known lignans (2-4, 7–11 ) as well as two caffeic-acid dimers (5, 6 ) were isolated from an ethanol extract of the whole plant of Corispermum mongolicum Iljin (Chenopodiaceae). The chemical structures of these compounds were determined from 1D and 2D NMR and HR-ESI-MS spectra, and results were compared with data from the literature. This study is the first demonstration of nine compounds (2 and 4 –11 ) isolated from the Chenopodiaceae family, with one of these (3 ) from the genus Corispermum . Anti-inflammatory effects of the isolated compounds were evaluated in terms of inhibition of production of nitric oxide, tumour necrosis factor-α, and interleukin-6 in lipopolysaccharide-induced RAW 264.7 cells. Abstract :